Manifestations of Folklore in Literature Learning: Comparative Study of Indonesia & Russia - Kurniawati, Erika; Dimitruk, Elena; Buchelnikova, Anna; Darni, Darni; Efendi, Agik Nur; Sari, Reny Yuanita (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Language and literature learning is closely related to character values ​​instilling to students. Character cultivation can be conveyed through literary works. Literary works containing character values not only come from Indonesian local culture, but it also folktales from Russian. This article aims to investigate the process of cultivating character education through learning literature containing folklore. The formal object of research was cultural theory with a comparative perspective. The material objects were the Damarwulan Folklore (Indonesia) and Цветок папоротника (Tsvetok Paporotnika or Fern Flower) folktale. Data that was taken were in the form of words, sentences, and paragraphs in Indonesian & Russian folktales. Data collection techniques in this research used reading and note-taking. The data analysis technique used in this research is to identify the research focus, interpret the data hermeneutically, and generalize the findings. The results of the research show that Indonesian and Russian folklore have relevant values, both among humans, oneself and nature.